The ‘The Secret’ behind Universality and Eternality of Sufism : Book Review of Sufisme East and West: Mystical Islam and Cross-Cultural Exchange in Modern World - Haq, Sansan Ziaul (Fakultas Seni Rupa dan Desain ITB, 2024)
What is Sufism? In simple terms, Sufism is a moral-spiritual aspect of Islamic teachings. When we attempt to define it, we encounter a scientific discourse about the ‘deepest secret’, which is significantly more intricate than we initially thought. Therefore, readers should independently investigate and draw their conclusions, which may include a comprehensive exploration of the book under review. Sufism, as a practice, teaches us how to feel the deepest secret intimately and substantially. Of course, capturing the breadth and abstractness of this experience in an instant definition anchor will be challenging, particularly when this mystical experience manifests in or intersects with Sufis’ moral choices in the social, political, economic, and cultural realms. Bruce B. Lawrence, at the end of this book, compares Sufism to an elephant in a dark room. Anyone who tries to guess it—with a particular approach, methodology, and scientific perspective—is not uncovering the whole thing, but only groping for partial reality as it appears in the gaps of his perception.